2021
DOI: 10.1111/icad.12499
|View full text |Cite
|
Sign up to set email alerts
|

Out of sight, out of mind: public and research interest in insects is negatively correlated with their conservation status

Abstract: Conservation ‘culturomics’ analyses changes in word frequencies within large digital sources to gain conservation insights. Studies of mammals and birds have found little correlation between conservation need and research effort or popular interest. In this study, we examine research and public interest in 9355 potentially endangered insect species from the Union for Conservation of Nature (IUCN) Red List. Using search counts from Google search, Google Scholar and Ngram as indicators of public and research int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Resolving the distribution of species is a key requirement to understand their diversity and behavioural ecology, but also the threats they face (Manne and Pimm 2001; Richardson and Whittaker 2010). Historically, conducting field surveys was one of the first research efforts to study biodiversity (Wallace 1876), and determining the occurrence of species is needed to understand and protect biodiversity (Wang et al 2021). Occurrence surveys are generally based on field surveys, automated monitoring, surveys via citizen science, and literature reviews (Fletcher Jr et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Resolving the distribution of species is a key requirement to understand their diversity and behavioural ecology, but also the threats they face (Manne and Pimm 2001; Richardson and Whittaker 2010). Historically, conducting field surveys was one of the first research efforts to study biodiversity (Wallace 1876), and determining the occurrence of species is needed to understand and protect biodiversity (Wang et al 2021). Occurrence surveys are generally based on field surveys, automated monitoring, surveys via citizen science, and literature reviews (Fletcher Jr et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…insects), yet their roles in the ecosystem are no smaller than the charismatic megafauna humans are naturally drawn to focus on; hence a conundrum for conservation biologists (Fisher 2019, Wang et al . 2021). Our study demonstrates that big data combined with machine learning could be used to help address our lack of knowledge about population trends for some species.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Correia et al (2016) found that familiarity (human population within the range of a species) is the most important factor for internet saliency in Brazilian birds; and Schuetz et al (2015) reported that, in the USA, people are more interested in species with high estimates of bird population densities. In addition, conservation status is negatively related to public interest in species, which suggests that low population size and lack of opportunities for observation could be factors (Correia et al 2016;Wang et al 2021). However, these variables are highly abstract as proxies for the distance between human society and wildlife, requiring a search for more practical variables.…”
Section: Introductionmentioning
confidence: 99%